Sustained Release Formulation of Primaquine for Prevention of Relapse of Plasmodium vivax Malaria: A Randomized, Double-Blind, Comparative, Multicentric Study. (20th August 2015) - Pareek, Anil; Chandurkar, Nitin; Gogtay, Nithya; Deshpande, Alaka; Kakrani, Arjun; Kaneria, Mala; Karmakar, Partha; Jain, Arvind; Kochar, Dhanpat; Chogle, Arun; Ray, Arnab
Abstract : Background . Primaquine is used to eradicate latent Plasmodium vivax parasite from liver, with administration of standard dose daily up to 14 days. We studied efficacy, safety, and tolerability of sustained release (SR) formulation of primaquine in comparison with conventional primaquine in preventing relapse of P. vivax malaria. Methods . Microscopically confirmed cases of P. vivax malaria received chloroquine therapy for three days. Aparasitemic and asymptomatic patients were then randomized to receive either conventional primaquine 15 mg for 14 days or primaquine SR 15 mg for 14 days, or primaquine SR 30 mg for seven days. Results . Of the 360 patients, who received chloroquine therapy, 358 patients were randomized. Two-hundred eighty-eight patients completed six-month follow-up and four patients (three: conventional primaquine 15 mg (2.86%), one: primaquine SR 30 mg (0.93%)) showed relapse confirmed by PCR genotyping. Drug compliance was significantly better in primaquine SR 30 mg group (95.57%, p = 0.039 ) without any serious adverse events. Conclusion . Primaquine SR 15 mg and primaquine SR 30 mg could be an effective alternative to conventional primaquine 15 mg due to their comparable cure rates and safety profile. Shorter treatment duration with primaquine SR 30 mg may increase patient compliance and may further reduce relapse rates. Clinical Trial Registration . This trial is registered withCTRI/2010/091/000245 .